Development Priority of Tanjung Tembaga Port with AHP (Analytical Herarchy Process) Method - Idris Albawavi; Hanie Teki Tjendani; Nurani Hartatik; Wahyu Agung Prihartanto; Deka Maheswara (Center for Research and Community Service (LPPM) University of Abulyatama, 2022)
The world of transportation’s development from time to time also demands development of its facilities and infrastructure, one of them is sea transportation. The port is a supporting facility for sea transportation that continues to develop to adapt to the demands of the times. The purpose of this research is to analyze the development potential of the Tanjung Tembaga Port which is then determined by the priority ranking of the options that have been obtained. This research using the AHP (Analytical Hierarchy Process) method in the form of a questionnaire addressed to the officials of PT. Pelabuhan Indonesia III Probolinggo. The results showed that the construction of a jetty was the most important thing to be realized immediately by obtaining a value of 29%, followed by the construction of a passenger terminal with a value of 22%, the application of the Greenport or Eco-port concept with a value of 19.5%, additional warehouse units with a value of 15.1%, construction of stacking yards with a value of 8.2%, and procurement of loading and unloading equipment with a value of 6.2%.